68Ga‐DOTATATE PET/CT imaging in endogenous hyperinsulinemic hypoglycemia: A tertiary endocrine centre experience. (8th September 2021) - Shah, Ravikumar; Sehemby, Manjeetkaur; Garg, Robin; Purandare, Nilendu; Hira, Priya; Mahajan, Abhishek; Lele, Vikram; Malhotra, Gaurav; Verma, Priyanka; Rojekar, Amey; Dalvi, Abhay; Uchino, Shinya; et al.
Abstract: Objective: Literature regarding utility of 68 Ga‐DOTATATE PET/CT in insulinoma localization across various subgroups [benign/malignant/multiple endocrine neoplasia‐1 (MEN‐1) syndrome associated] remains scarce. In this study, the performance of 68 Ga‐DOTATATE PET/CT was compared with contrast‐enhanced computed tomography (CECT) and 68 Ga‐NODAGA‐Exendin‐4 PET/CT (whenever available) in an endogenous hyperinsulinemic hypoglycemia (EHH) cohort. Design: Retrospective audit. Patients: EHH patients [ N  = 36, lesions ( n ) = 49, final diagnosis: benign sporadic insulinoma (BSI) ( N  = 20), malignant insulinoma ( N  = 4, n  = 14), MEN‐1 syndrome associated insulinoma ( N  = 9, n  = 15), Munchausen syndrome ( N  = 2) and drug‐induced hypoglycemia ( N  = 1)] having both preoperative imaging modalities (CECT and 68 Ga‐DOTATATE PET/CT). Measurements: Per‐lesion sensitivity (Sn) and positive predictive value (PPV) for histopathological diagnosis of insulinoma. Results: Sn and PPV of 68 Ga‐DOTATATE PET/CT were 67.3% and 89.2%; 55% and 100%; 85.7% and 100%; and 66.7% and 77% for overall EHH, BSI, malignant, and MEN‐1 syndrome associated insulinoma cohorts respectively. Despite having comparatively lower sensitivity in BSI cohort, 68 Ga‐DOTATATE PET/CT localized a pancreatic tail lesion missed by other modalities. 68 Ga‐DOTATATE PET/CT had comparatively higher sensitivity in malignant insulinoma than BSI cohort. 68 Ga‐DOTATATE PET/CT also paved the way for successful response to 177 Lu‐based peptide receptor radionuclide therapy (PRRT). In MEN‐1 cases, lower PPV as compared with BSI was due to uptake in non‐insulinoma pancreatic neuroendocrine tumours (Pan‐NET). Conclusions: 68 Ga‐DOTATATE PET/CT has supplemental role in selected cases of BSI with negative and/or discordant results with CECT and 68 Ga‐NODAGA‐Exendin‐4 PET/CT. In malignant insulinoma, 68 Ga‐DOTATATE‐PET/CT has an additional theranostic potential. Interference due to uptake in non‐insulinoma Pan‐NET in MEN‐1 syndrome may hinder insulinoma localization with 68 Ga‐DOTATATE‐PET/CT.